How the design of retail prices, network charges, and levies affects profitability and operation of small-scale PV-battery storage system - Jessica Thomsen; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
We assess how the design of retail prices, network charges and levies for household prosumers affect the attractiveness and resulting operation of small-scale photovoltaic battery storage systems (PVBSS), using a detailed modeling approach applied to a case study of six households in Germany. The selected pricing schemes and reform proposals are evaluated regarding the investment attractiveness for the prosumer and the impact on system-oriented operation, considering both market and grid integration. We show that currently the business case for PV as well as PVBSS only exists since it allows avoiding grid offtake and thus avoiding paying taxes and levies on consumed electricity. Introducing time-variable pricing schemes or price components increases the value of PVBSS for the customer and the market, but leads to less grid-friendly operation. It is shown that the term "system-oriented operation" should be defined carefully since market value and grid-friendly operation do not necessarily go hand in hand so that one incentive cannot inherently contribute to both objectives at the same time. The tariff design, as well as the design of single tariff components have a considerable impact on the attractiveness and the resulting system integration of PVBSS and should be evaluated thoroughly to avoid unintended outcomes.
Keywords: 330; photovoltaic battery storage systems; tariff design; system integration; grid integration